Evaluation of Giant and Neotropical Otter as environmental assets in Conservation Tourism based on emergy analysis - Carvalho Junior, Oldemar; Bez Birolo, Alesandra (Goodwood Publishing, 2021)
Purpose: The main objective of this work is to evaluate the natural capital and ecosystem services of the Aquidauana River and the role of Lontra longicaudis and Pteronura brasiliensis as environmental assets for the development of conservation tourism. Research Methodology: First, a system diagram was built to organize ideas and relationships between components and resource flows. Second, it was to construct tables of emergy flows directly from the diagrams. Quantities of stored emergy of environmental resources are calculated from the sum of the emergy of all inputs and then multiplied by the time it takes to accumulate the storage. Results: The main services with market values ??provided by the Aquidauana River are water supply, tourism, and fishing. The neotropical otter exhibited the largest asset in the system, followed by the giant otter and the indigenous culture. Limitations: Application of the emergy method to define public policies that lead to the real valuation of environmental assets and promote the social mobilization needed to change adverse realities. Contribution: The giant otter and neotropical otter values represent more than 90% of all values listed as environmental assets in the Aquidauana River System. The results can be important for the definition of public policies aimed at conservation tourism. With an appropriate social mobilization program, associated with economic and environmental education, the local economy could be strengthened, along with the protection of biodiversity.